Microfinance, EU Structural Funds and Capacity Building for Managing Authorities A Comparative Analysis of European Convergence Regions - Pes, Giovanni Nicola; Porretta, Pasqualina (Springer Nature, 2015)
Finance and Banking, General Finance, International Finance